ESTABLISHMENT OF INDIVIDUAL CONSONANCE IN MAKASSAR MUSLIM COMMUNITIES ON CONDOMS THROUGH LOCAL FUNCTION INSTITUTION - Adam Badwi; Munadhir Munadhir (Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to analyze the factors that influence the occurrence of individual cognitive dissonance in the community towards condoms in the city of Makassar through a quantitative approach to analytical design. The location of the study was in Makassar City on the grounds that Makassar City had the largest HIV and AIDS cases in South Sulawesi, the level of condom use was still very low, the HIV / AIDS epidemic rate was very high in the last 3 years, especially in the pattern of HIV and AIDS transmission through sex heterosexual. The results found that religious norms, cultural values and experience of condom use have an influence on the occurrence of individual cognitive dissonance towards the condom and experience of condom use is the most dominant factor affecting the occurrence of individual cognitive dissonance in the condom.